Imperfect Competition and Corporate Governance - Frank Milne; David Kelsey (Queen's University, Department of Economics, 2006)
This paper studies corporate governance when a firm operates in imperfect markets. We derive firms' decisions from utility maximization by individuals. If those involved in decisions are also consumers, the usual monopoly distortion is reduced. Corporate governance can effect the equilibrium in the product (or input) markets. This enables us to endogenize the objective function of the firm. If the firm cannot commit not to change its constitution, we find a Coase-like result where all market power is lost in the limit. We present a more abstract model of governance in the presence of market distortions.
Keywords: D70; L13; L20; 330; corporate governance; stakeholder; oligopoly; strategic delegation; Corporate Governance; Unvollkommener Wettbewerb; Preisdifferenzierung; Stakeholder; Theorie